Business dashboards : a visual catalog for design and deployment - Rasmussen, Nils, 1964-; Chen, Claire Y., 1965-; Bansal, Manish, 1974- (Hoboken, N.J. : John Wiley & Sons, 2009)
Focusing on designing the right dashboards for use in an organization, this timely book reveals how to successfully deploy dashboards by building the optimal software architecture and dashboard design. In addition, it describes the value of this popular technology to a business and how it can have a significant impact on performance improvement. Numerous real-life dashboard images are organized by category as well as examples of performance measures to help design the content of dashboards. The book also describes all the steps in a dashboard implementation and offers related advice. Nils Rasm.
chapter 8: Why a Good Architecture Is Importantchapter 9: Data Warehouse Techniques; chapter 10: Data Replication and Delivery; chapter 11: Query Language and Interactivity; chapter 12: Data Warehouse and Business Intelligence Dashboard Paradigm; chapter 13: Mobile Business Intelligence; PART 2 SUMMARY AND READINESS CHECKLIST; PART 3: DASHBOARD DESIGN; chapter 14: Design Tips; chapter 15: Dashboard Examples; PART 3 SUMMARY AND READIN.
Includes index.
Print version record.
English.
John Wiley and Sons
Keywords: Dashboards (Management information systems); Balanced scorecard (Management); Tableaux de bord (Gestion); COMPUTERS -- Management Information Systems; Balanced scorecard (Management); Dashboards (Management information systems)